Strategi Fundraising dalam Pembangunan Sarana Pendidikan di SMA Negeri 1 Kedungwuni - Muhammad Nabhan Fajruddin (Advances In Education Journal, 2025)
In an educational institution, costs are required to develop learning support facilities in schools. Apart from BOS and Bosda funds, schools must be able to raise funds to meet learning facility needs. Including sports field facilities which are facilities that support student learning. This research contains fundraising strategies in financing sports fields at SMA Negeri 1 Kedungwuni. Through descriptive qualitative methods, researchers found out about the fundraising strategies used to finance sports fields at SMA Negeri 1 Kedungwuni. The results of this research explain that the strategies used in raising funds to finance sports fields are as follows; through alumni, school committees, Friday donations, and sponsors. The aim of this research is to improve the quality of education through fundraising strategies in the construction of sports fields. Adequate sports field facilities will produce good quality education.